Quality of Life Based on Autologous Serum Skin Test Result in Chronic Spontaneous Urticaria Patients - Mahvira Chow Liana Herman Adil; Nopriyanti; Desi Oktariana; Yuli Kurniawati; Gita Dwi Prasasty (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Several studies regarding the quality of life of chronic spontaneous urticaria patients based on Autologous Serum Skin Test (ASST) results have shown a variety of results. This study aims to determine the correlation between the quality of life and ASST results in chronic spontaneous urticaria patients at Dermatology and Venereology (DV) Outpatient Clinic of Dr. Mohammad Hoesin Hospital Palembang. This analytic observational study with a cross-sectional design used secondary data in the form of medical records. 76 samples met the inclusion criteria from 110 samples of chronic spontaneous urticaria patients at DV outpatient clinic. The distribution of chronic spontaneous urticaria patients was highest in the 17-25 year age group (23.7%) and the female group (64.5%). The majority of chronic spontaneous urticaria patients had negative ASST results (52.6%). The effect of chronic spontaneous urticaria on the decline in quality of life was mostly moderate (35.5%). The bivariate analysis between DLQI score and ASST results with a value of p = 0.307 or p> 0.05 showed no significant correlation between the quality of life and ASST results.